The Ox the authorized biography of The Who's John Entwistle - Rees, Paul (Hachette Books, 2020)
"The definitive, no-holds-barred biography of John Entwistle, The Who's legendary bass guitarist. It is an unequivocal fact that in terms of rock bands, the Beatles, the Rolling Stones and the Who represent Year Zero; the beginning of all things, ground-breakers all. To that incontrovertible end, John Entwistle- The Who's beloved bassist- remains an enigmatic yet undeniably influential figure. However, unlike his fellow musicians, Entwistle has yet to be the subject of a major biography. In the years since his death, his enduring legacy has been carefully guarded by his loved ones, preventing potential biographers from gaining close enough access to write a definitive account of his life- until now. For the first time, and with the full co-operation of the Entwistle family, The Ox shines a long overdue light on one of the most important figures in rock history."--Cover flap
Keywords: Entwistle, John -- 1944-2002; The Who -- Musikgruppe; Geschichte 1944-2002; Rockmusik; Gitarrist; Großbritannien; Entwistle, John / 1944-2002; Who (Musical group); Rock musicians / Great Britain / Biography; Bass guitarists / Biography; Bass guitarists; Rock musicians; Great Britain; Biographies; Biografie